IoT-Based Fire Detection System Using a Flame Detector and Arduino Uno R4 WiFi - Dewi, Ratih; Fadhliansyah, Ivan; Ma'rufi, Riado; Lubis, Dwiki Ar-Raiyyan (ULTIMA Computing, 2025)
According to data from the DORS POLRI application, there were 935 fire incidents recorded from January to October 7, 2024. Based on these data, a fire detection security system with early warning capabilities is needed to mitigate fire risks and prevent casualties. The system designed in this study is IoT-based, which sends notifications via Telegram when a fire is detected.The results of this research show that by reducing the sensor sensitivity to 33%, the sensor still performs well in detecting fire — it can detect a flame at a distance of 35 cm and detect light from an incandescent bulb at approximately 95 cm. However, the sensor cannot detect paraffin flames at distances of 10–50 cm because the paraffin flame’s wavelength lies outside the detectable range of the sensor.Thus, this system has proven effective in detecting fire and providing real-time automatic notifications via Telegram, allowing users to respond quickly when potential fire hazards occur.